2010
DOI: 10.3113/fai.2010.0247
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ankle Pain Secondary to Talus Partitus: Two Case Reports

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
1
14
0
1
Order By: Relevance
“…Consequently, the resulting ossicle was broader on the lateral side because of the bigger size of the lateral tubercle of the posterior process as compared with the medial tubercle. These findings are consistent with the findings of the single axial CT images shown in two previous case reports 5,7 . Because all six cases were associated with an oblique course of the cleft, the term ''frontal split'' seems inaccurate and would best not be used as a synonym for this skeletal variant.…”
Section: E21(4)supporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, the resulting ossicle was broader on the lateral side because of the bigger size of the lateral tubercle of the posterior process as compared with the medial tubercle. These findings are consistent with the findings of the single axial CT images shown in two previous case reports 5,7 . Because all six cases were associated with an oblique course of the cleft, the term ''frontal split'' seems inaccurate and would best not be used as a synonym for this skeletal variant.…”
Section: E21(4)supporting
confidence: 93%
“…Short-term pain relief was reported, but pain recurred two years later along with 10°of restriction of ankle dorsiflexion. Recently, Eichenbaum et al 7 reported on two patients with symptomatic talus bipartitus. In an eighteen-year-old man who had a history of ankle pain for more than four years, surgical exploration revealed a dysmorphic fragment with signs of arthritis at the subtalar joint.…”
Section: E21(4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Dorsal flexion TCR, restr. ROM STJ, pain4X-ray, arthrographyTB, flattened talar domeBoth joints involvedBlauth [5]198718FLeftPain during activityRestricted ROM AJNo2X-rayTB, sclerotic, congruent1/3 talar dome, both joints involvedGriffet [7]200315FLeftIntermittent ankle pain during activityNormalNo1X-ray, MRITB, incongruent fragments both joints, degenerative, aberrant aspect calcaneusPosterior 1/3 of talar bodySubtalar arthrodesisDecrease pain, recurrence after 2 y, conservatively treated2Eichenbaum [14]201018MRightIncreasing hindfoot painFROM TCJ, painful restricted ROM STJNo4X-ray, CTTB, degenerative changes4 × 2 × 1.5 cm, 50% post STJExcision + subtalar arthrodesisPain-free activity116MRightAnkle pain and instabilityIncreased ROM STJ, instabilitySprain1.2X-ray, CT, MRITB, sclerotic irregular margins2.8 × 1.1 × 0.8 cmExcisionPain and instability improved0.5Thiel [8]201012…”
Section: Resultsmentioning
confidence: 99%